Crack growth modeling of tension lap spliced reinforced concrete beams strengthened with fibre reinforced polymer wrapping under fatigue loading. (30th March 2018) - Alyousef, Rayed; Topper, Tim; Al-Mayah, Adil
Highlights: A crack growth model has been developed to strengthened and unstrengthen RC beam with lap splice under fatigue loading. A linear relationship found between the constant α from the crack growth parameter and the monotonic average shear stress, as the average shear stress increases the value of the α decreases. The average shear stress of the monotonic test results fell close to the intercept of the shear stress – fatigue life curve on logarithmic – logarithmic scales at one cycle. There is a good agreement between the calculated number of cycles and the actual fatigue data for all tested beam. Abstract: This study was aimed at increasing our understanding of the behavior of the bond between a steel bar and the concrete along a lap splice region for structures subjected to cyclic loading. An additional aim of the study was to investigate the effect of fatigue loading on the bond between concrete and steel, and the ability of the new high and low modulus fiber-reinforced polymer (FRP) sheets to enhance the fatigue performance of a tension lap splice. A crack growth model was developed to calculate the fatigue life of the bond specimens. The model results were compared with the experimental outcomes of fifty-three beams tested under fatigue and monotonic loading. There is a good agreement between the calculated number of cycles and the actual fatigue life data for all different wrapping conditions and different concrete cover thicknesses. The difference between the calculated and measured fatigue strength curves did not exceed seven percent.